Minimally Invasive Esophagectomy. Issue 4 (April 2015) - Luketich, James D.; Pennathur, Arjun; Franchetti, Yoko; Catalano, Paul J.; Swanson, Scott; Sugarbaker, David J.; De Hoyos, Alberto; Maddaus, Michael A.; Nguyen, Ninh T.; Benson, Al B.; Fernando, Hiran C.
<x xml:space="preserve">Abstract</x> Objective: The primary aim of this trial was to assess the feasibility of minimally invasive esophagectomy (MIE) in a multi-institutional setting. Background: Esophagectomy is an important, potentially curative treatment for localized esophageal cancer, but is a complex operation. MIE may decrease the morbidity and mortality of resection, and single-institution studies have demonstrated successful outcomes with MIE. Methods: We conducted a multicenter, phase II, prospective, cooperative group study (coordinated by the Eastern Cooperative Oncology Group) to evaluate the feasibility of MIE. Patients with biopsy-proven high-grade dysplasia or esophageal cancer were enrolled at 17 credentialed sites. Protocol surgery consisted of either 3-stage MIE or Ivor Lewis MIE. The primary end point was 30-day mortality. Secondary end points included adverse events, duration of hospital-stay, and 3-year outcomes. Results: Protocol surgery was completed in 95 of the 104 patients eligible for the primary analysis (91.3%). The 30-day mortality in eligible patients who underwent MIE was 2.1%; perioperative mortality in all registered patients eligible for primary analysis was 2.9%. Median intensive care unit and hospital stay were 2 and 9 days, respectively. Grade 3 or higher adverse events included anastomotic leak (8.6%), acute respiratory distress syndrome (5.7%), pneumonitis (3.8%), and atrial fibrillation (2.9%). At a median follow-up of 35.8 months, the estimated 3-year overall survival was 58.4% (95% confidence interval: 47.7%–67.6%). Locoregional recurrence occurred in only 7 patients (6.7%). Conclusions: This prospective multicenter study demonstrated that MIE is feasible and safe with low perioperative morbidity and mortality and good oncological results. This approach can be adopted by other centers with appropriate expertise in open esophagectomy and minimally invasive surgery.